External and local controls on land-sea coupling assessed by stable isotopic signatures of mangrove producers in estuaries of Pacific Panama. (June 2018) - Valiela, Ivan; Pascual, Jesús; Giblin, Anne; Barth-Jensen, Coralie; Martinetto, Paulina; Otter, Marshall; Stone, Thomas; Tucker, Jane; Bartholomew, Megan; Viana, Inés G.
Abstract: Foliar stable isotopic signatures of nitrogen, carbon, and sulfur in mangrove vegetation from the Pacific coast of Panama were insensitive to inputs from watersheds with different area of forest land cover, and to seasonal, inter-annual, and global-scale-driven contrasts in rainfall and upwelling. N, C, and S content of mangrove vegetation were not affected by inputs from watersheds with different degrees of deforestation, but showed some influence of down-estuary transformations. While there was substantial variation that remained un-explained, isotopic signatures and nutrient contents were largely determined by species-specific features, and showed substantial small-scale variation reflecting local differences, within-estuary plant-sediment links. The ability of mangrove estuaries to erase effects of deforestation points out that conservation of these wetland ecosystems is important, because, at least in the sites we studied, transformations within mangrove estuaries were strong enough to protect water quality in receiving coastal waters. Highlights: External variables failed to alter stable isotope values in mangrove leaves. Foliar stable isotopic values were insensitive to different forest cover watersheds. Mangrove isotopic signatures changed down-estuary and at small scale. Foliar N isotopic signature was related with sediment N isotopic signatures. Nutrient contents were determined by species-specific features.